Regional homogeneity changes in amnestic mild cognitive impairment patients. (26th August 2016) - Yuan, Xiaoling; Han, Ying; Wei, Yongbin; Xia, Mingrui; Sheng, Can; Jia, Jianping; He, Yong
Highlights: The aMCI patients showed abnormal ReHo values in temporal, parietal and occipital lobes by examining spontaneous brain activity during rest state. Regional brain atrophy may act as a necessary consideration during the functional imaging studies of aMCI patients. ReHo measurement could be a biomarker for the early diagnosis of aMCI. Abstract: Objective: Regional Homogeneity (ReHo) measures the local coherence of spontaneous brain activity, and it is sensitive to detect aberrant local functional connectivity of brain region. We tried to explore the activity of brain network by ReHo method in amnestic mild cognitive impairment (aMCI) patients and examine the impact of regional brain atrophy on the functional results. Methods: Data of both structural magnetic resonance images (MRI) and resting-state functional MRI scans were collected from 36 aMCI patients and 46 age-matched healthy controls. Results: Compared with the HC subjects, the aMCI patients showed significant decreased ReHo areas in the right inferior parietal lobule (IPL), left posterior cingulate cortex/precuneus (PCC/PCu), left inferior temporal gyrus (ITG), right supramarginal gyrus (SMG), right fusiform gyrus (FG), bilateral lentiform nucleus (LN) and right cerebellum posterior lobe, with the right IPL being the most significant area. In addition, the aMCI group also had some significant increased ReHo areas in the right medial frontal gyrus (MFG), bilateral postcentral gyrus (PoCG), left cuneus and right lingual gyrus (LG), possibly reflective of some underlining compensatory mechanism. Furthermore, in the aMCI patients, we found the ReHo index of the left PCC was positively correlated with the AVLT-Immediate Recall scores, while the ReHo index of the left cuneus was negatively correlated with the MMSE scores. In addition, we found that after regressing out the identified regional brain atrophy, the significant correlations between fitted ReHo index and clinical variables still remained. Conclusions: Our study indicated that aMCI patients showed significant abnormal local coherence of biological activity in resting state and ReHo could serve as a sensitive biomarker in functional imaging studies of aMCI.